Effect of intra‐operative intravenous lidocaine on opioid consumption after bariatric surgery: a prospective, randomised, blinded, placebo‐controlled study. (21st June 2020) - Plass, F.; Nicolle, C.; Zamparini, M.; Al Issa, G.; Fiant, A. L.; Le Roux, Y.; Gérard, J. L.; Fischer, M. O.; Alvès, A.; Hanouz, J.‐L.
Summary: Peri‐operative lidocaine infusion warrants investigation in bariatric surgery because obese patients present different physiological and pharmacological risks. This single‐centre, prospective, randomised double‐blind placebo‐controlled study enrolled obese patients scheduled for laparoscopic bariatric surgery using an enhanced recovery protocol. Patients received either lidocaine (bolus of 1.5 mg.kg −1, then a continuous infusion of 2 mg.kg −1 .h −1 until the end of the surgery, then 1 mg.kg −1 .h −1 for 1 h in the recovery area) or identical volumes and rates of 0.9% saline. The primary outcome was the consumption of the equivalent of oxycodone consumption over the first 3 postoperative days. Secondary outcomes were: postoperative pain; incidence of nausea and vomiting; bowel function recovery; and lengths of stay in the recovery area and in hospital. Plasma concentrations of lidocaine were measured. On the 178 patients recruited, data were analysed from 176. The median (IQR [range]) equivalent intravenous oxycodone consumption was 3.3 mg (0.0–6.0 [0.0–14.5]) and 5.0 mg (3.3–7.0 [3.3–20.0]) in the lidocaine and saline groups, respectively (difference between medians (95%CI): 1.7 (0.6–3.4) mg; p = 0.004). Length of stay in the recovery area, postoperative pain, nausea and vomiting, day of recovery of bowel function, and length of stay in hospital were not different between groups. Mean (SD) lidocaine plasma concentrations were 2.44 (0.70) µg.ml −1 and 1.77 (0.51) µg.ml −1 at the end of surgery and 1 hour after the end of infusion, respectively. Lidocaine infusion during bariatric surgery resulted in a clinically non‐relevant difference in postoperative oxycodone consumption.